Robust intelligent active force control of nonholonomic wheeled mobile robot - Tang, H. H.; Mailah, Musa; A. Jalil, M. Kasim (Penerbit UTM Press, 2006)
The paper describes a new and novel approach to control a nonholonomic wheeled mobile robot (WMR) robustly with reference to its trajectory tracking capability in the wake of introduced disturbances. The workspace of a mobile robot is not always ideal but more often than not, filled with disturbances (known or unknown) such as inherent friction, irregular surface terrain, uncertainties, and parametric changes. An intelligent active force control (IAFC) scheme incorporating fuzzy logic has been proposed in the study to counter the disturbances and consequently improve the trajectory tracking characteristic of the system. In the study, IAFC scheme is employed together with a resolved acceleration control (RAC) that has been shown to provide a very robust and accurate performance of the WMR. Fuzzy logic is explicitly used for the estimation of the inertia matrix that is required in the inner feedback control loop of the IAFC scheme. The robustness and effectiveness of the proposed control scheme are investigated considering various forms of loading and operating conditions. The IAFC scheme has also been compared to two other control methods for the purpose of benchmarking.